Correction: Application of a Mixed Methods Multi- Criteria Decision Analysis Framework in Integrated Health Care - Robin Blythe; Hannah Carter; Bridget Abell; Megan Campbell; David Brain; Carly Dyer; Nicole White; Sanjeewa Kularatna; Steven McPhail (International Journal of Integrated Care, 2022)
This article details a correction to: Blythe R, Carter H, Abell B, Brain D, Dyer C, White N, et al. Application of a Mixed Methods Multi-Criteria Decision Analysis Framework in Integrated Health Care. 'International Journal of Integrated Care'. 2022; 22: 19. DOI: http://doi.org/10.5334/ijic.5997.